2008
DOI: 10.1108/13522750810845568
|View full text |Cite
|
Sign up to set email alerts
|

CAQDAS: a supplementary tool for qualitative market research

Abstract: Purpose 1) To assess the usage of CAQDAS (Computer Assisted Qualitative Data AnalysiS) in the UK market research industry, and 2) To evaluate the use of CAQDAS as a supplement to paper-coding in market research. Design/methodology/approach CAQDAS usage was assessed by a questionnaire, sent to a sample of 400 UK market researchers. The second part of the research is a case study of a research experiment. We conducted focus group research into online grocery shopping, supplementing a paper-coding based analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 16 publications
0
26
0
4
Order By: Relevance
“…Some of the concerns raised in literature indicated that most of the negative attitudes might be as a result of misperceptions about how the software is generally applied as well as a concern that the data analysis part will be done by the program itself. This resistance might be due to the fact that research indicates minimal application of QDA programs even though researchers are aware of it (Rettie, Robinson, Radke, & Ye, 2008).…”
Section: The Use Of Qualitative Data Analysis (Qda) Programs In Gtmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the concerns raised in literature indicated that most of the negative attitudes might be as a result of misperceptions about how the software is generally applied as well as a concern that the data analysis part will be done by the program itself. This resistance might be due to the fact that research indicates minimal application of QDA programs even though researchers are aware of it (Rettie, Robinson, Radke, & Ye, 2008).…”
Section: The Use Of Qualitative Data Analysis (Qda) Programs In Gtmentioning
confidence: 99%
“…A possible solution to this is the use of qualitative data analysis (QDA) 1 programs (Bowen, 2005) or computer assisted qualitative data analysis software (CAQDAS) (Rettie, Robinson, Radke, & Ye, 2008). However, much controversy exists on the use of these software programs as these programs are not universally accepted (Atherton & Elsmore, 2007).…”
Section: The Use Of Qualitative Data Analysis (Qda) Programs In Gtmentioning
confidence: 99%
See 3 more Smart Citations